2020
DOI: 10.3390/ijms21155348
|View full text |Cite
|
Sign up to set email alerts
|

Selective Transport of Ag(I) through a Polymer Inclusion Membrane Containing a Calix[4]pyrrole Derivative from Nitrate Aqueous Solutions

Abstract: Cellulose-triacetate-based polymer inclusion membranes (PIMs) with different concentrations of a calixpyrrole ester derivative as the membrane carrier were studied to determine their ability to transport Ag(I) from aqueous nitrate solutions. The effects of the concentrations of ion carriers and metal ions, the pH of the source aqueous phase, and stripping agents on the effective transport of Ag(I) were assessed. All studied parameters were found to be important factors for the transport of Ag(I) metal ions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…This thematic area is associated with articles [ 12 , 15 , 20 , 21 , 26 , 50 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], of which there are a total of 50. In contrast to the areas already discussed above, articles of all four types are presented here ( Table 5 ), although, here, too, the Original constitutes a clear majority over the other 3 types of articles.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This thematic area is associated with articles [ 12 , 15 , 20 , 21 , 26 , 50 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], of which there are a total of 50. In contrast to the areas already discussed above, articles of all four types are presented here ( Table 5 ), although, here, too, the Original constitutes a clear majority over the other 3 types of articles.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…In contrast to the areas already discussed above, articles of all four types are presented here ( Table 5 ), although, here, too, the Original constitutes a clear majority over the other 3 types of articles. The dominant feature of this thematic area was articles devoted to cell membranes, in general, and their electrochemistry, in particular; articles [ 26 , 50 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 92 , 93 , 95 , 99 , 100 ] are devoted to this specific topic. In this connection, it is worth noting that this “membrane topic” turned out to be, generally, the most popular in comparison with all the others presented in the PCCP Section of the IJMS , within the array of 300 articles we are considering.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…Kozłowski et al used PIMs equipped with Calix[4]pyrrole derivative as a carrier for the separation of Ag(I) from different nitrate aqueous solutions. They found that the effective transport of silver ions depends on many factors—not only on the concentrations of the carriers and metal ions, but also on the pH and temperature of the source aqueous phase [ 32 ]. Because separation processes based on the application of PIMs and other polymer sorbents are influenced by many parameters [ 24 , 27 ], it is extremely important to compare the effectiveness of polymer materials with specific carriers in model and real solutions.…”
Section: Introductionmentioning
confidence: 99%
“…There are publications aimed at the preparation and study of novel artificial membranes [ 5 , 6 , 7 , 8 , 9 , 10 ]. M. Mofasserul Alam et al [ 5 ] prepared and studied a novel anion-exchange membrane designed to separate bisulfite anion from mixt solutions.…”
mentioning
confidence: 99%
“…The developed process can be used for the production of fertilizers from wastewater. The ability of a series of cellulose-triacetate-based polymer inclusion membranes (PIMs) to transport Ag (I) was studied by A. Nowik-Zajac et al [ 10 ]. The membranes differed by different concentrations of a calixpyrrole ester derivative as the membrane carrier.…”
mentioning
confidence: 99%